Effective Quality School Management Strategies, Under the Office of Nakhon Ratchasima Primary Educational Service Area - Sudsaart, Sanong; Paengthai, Sasirada (Journal of Graduate MCU KhonKaen Campus, 2019)
This research aimed to, 1) Study the elements of the effective quality school management, under the Office of NakhonRatchasima Primary Educational Service Area. 2) Study current and desirable conditions and the external environment in the effective quality school management, under the Office of NakhonRatchasima Primary Educational Service Area. 3) Develop the effective quality school management strategies, under the Office of NakhonRatchasima Primary Educational Service Area. The samples used in the study were 302 public schools under the Office of NakhonRatchasima Primary Educational Service Area. The tools used for data collection were questionnaires and the evaluation of the appropriateness and possibility of the strategy. Data were analyzed by frequency, percentage, mean, standard deviation, PNI Modified index. The results showed that 1. The elements of the effective quality school management, under the Office of NakhonRatchasima Primary Educational Service Area, were of four components : 1) Management, 2) Learning, 3) Environment, 4) Participation.